RUANG KETIGA DAN KONSEP KONTEKSTUAL PERANCANGAN RUANG SENI DI SENEN - Fille Tamalazare Yuma; Maria Veronica Gandha (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2020)
In the modern era, the loss of third place in the city center, such as the city of Jakarta, has resulted in increasingly mushrooming shopping centers and increasing market gimmicks. This causes the level of social interaction between fellow humans decreases so that exclusivity is formed in each individual. In meeting social needs in that era, a social forum is needed as a place for communities to eliminate exclusivity and restore human nature which is basically a social creature that needs to interact. From this, architecture talks about ways to meet the needs of the community in the third place as a means of community existence. The presence of Art Space is intended to present communities where individuals can fuse and increase social interaction. Art Space raised the topic of art which is one of the characteristics of the Senen Kelurahan, Senen District, Central Jakarta. Art will be used as a medium and a tool to interact and communicate with each other. Making an entertainment center for art that is inclusive so that it can be enjoyed by all groups of people both artists, connoisseurs of art or the general public. The choice of performing arts is based on the high public interest in the Senen Village. The design of Art Space is designed with site analysis method so that the building pays attention to the surrounding context so as to strengthen the contextual concept. Combining typologies adapted from the habits or approaches of the needs of the surrounding community. Bluring boundaries between private closeness and public opensess. It is expected that Art Space can attract people to visit so that it presents social interaction. Keywords: Art Space; Social Interaction; Third Place Abstrak Pada era yang serba modern hilangnya third place pada pusat kota seperti kota Jakarta mengakibatkan pusat perbelanjaan semakin menjamur dan market gimmick yang terus meningkat. Hal tersebut menyebabkan tingkat interaksi sosial antara sesama manusia menurun sehingga terbentuklah eksklusifitas pada setiap individu. Dalam pemenuhan kebutuhan sosial di era tersebut, maka dibutuhkan wadah sosial sebagai wadah komunitas-komunitas untuk menghilangkan ekslusifitas dan mengembalikan hakekat manusia yang pada dasarnya adalah mahluk sosial yang perlu berinteraksi. Dari hal tersebut, arsitektur berbicara tentang cara untuk memenuhi kebutuhan komunitas pada third place sebagai sarana eksistensi masyarakat. Kehadiran Art Space dimaksudkan untuk menghadirkan komunitas-komunitas  di mana individu dapat melebur dan meningkatkan interaksi sosial. Art Space  mengangkat topik seni yang merupakan salah satu karakteristik kawasan Kelurahan Senen, Kecamatan Senen, Jakarta Pusat. Seni akan digunakan sebagai media dan alat untuk berinteraksi serta berkomunikasi antara sesama manusia. Menjadikan pusat hiburan seni yang inklusif sehingga dapat dinikmati oleh seluruh golongan masyarakat baik seniman, penikmat seni atau khalayak umum. Pemilihan jenis seni pertunjukan didasarkan oleh tingginya animo masyarakat pada Kelurahan Senen. Perancangan Art Space didesain dengan metode site analysis agar bangunan memperhatikan konteks sekitar sehingga memperkuat konsep kontekstual. Mengkombinasikan tipologi yang diadaptasi dari kebiasaan atau pendekatan kebutuhan masyarakat sekitar. Meleburkan batasan diantara private closeness dan public opensess. Diharapkan Art Space dapat menarik masyarakat untuk berkunjung sehingga menghadirkan interaksi sosial.